Victimization due to Sloppy investigation - Bhagavathy, P.G. Sunanda (International Journal of Psychosocial Rehabilitation, 2020)
The Criminal Procedure Code 235 (1) stresses that the threshold of evidence be raised beyond reasonable doubt so as to reduce the risk of false convictions. By raising the standard of proof, more criminals are likely to escape the clutches of Law, weakening the incapacitating and deterrent impact of the criminal justice system. The researcher’s study shows that many of the analysed cases ended in acquittal on flimsy grounds and some of the cases in honourable acquittal due to shoddy investigation. Connection between the crime and the criminal has to be proved beyond reasonable doubts so the victim satisfaction, the prime aim of the CJS is established. The joined endeavor of the Criminal justice system will prove to be a friend, philosopher and guide to the victims, the gate keepers of the CJS often